Anterolateral Thigh Flap for Reconstruction in Postburn Axillary Contractures. Issue 2 (August 2017) - Chen, Hung Chang; Wu, Katie P.; Yen, Cheng-I; Hsiao, Yen-Chang; Yang, Shih-Yi; Yang, Jui-Yung; Chang, Cheng-Jen; Chang, Shu-Yin; Chuang, Shiow-Shuh
Abstract : Background: Reconstruction of postburn axillary contractures is difficult and particularly challenging without healthy adjacent soft tissue for axillary scar resurfacing. In this case, a free soft-tissue transfer is among the best treatment options. Here, we describe our experience with free anterolateral thigh (ALT) flap for reconstruction in postburn axillary contractures. Methods: We enrolled 10 patients with postburn axillary contractures from August 2003 to July 2015. They all underwent wide scar contracture release through a transverse incision from the anterior axillary fold to the posterior axillary fold. The ALT flap was subfascially raised. The huge soft tissue defect after scar release was resurfaced with the ALT flap. Results: Eight male patients and 2 female patients (age, 16–64 years; mean, 46 years) were included. The mean total burn surface area, follow-up time, duration between injury onset and free-flap transfer surgery, and flap size were 48%, 27 months, 7.7 months, and 12 × 23 cm 2, respectively. The most common recipient vessels were the thoracodorsal artery and vein (77%). The mean improvement in the range of motion of shoulder abduction was 86 degrees (range, 60–130 degrees). The mean operative time was 7 hours. All flaps survived without reexploration or failure. All but 1 donor site was managed by split-thickness skin grafting. No infection, hematoma, or deaths were noted postoperatively. Transient brachial palsy was noted in a 16-year-old male patient postoperatively, with full recovery 3 months after. Conclusions: For postburn axillary contractures without healthy adjacent soft tissue for scar resurfacing, ALT flap reconstruction represents a suitable treatment option. It allows simultaneous surgery on both the donor and recipient sites, without the need to change the patient's position. Furthermore, the ALT flap provides sufficient soft tissue and blood flow for reconstruction, leading to satisfactory functional outcomes.